Characterizing the proximal esophageal segment in patients with symptoms of esophageal dysmotility. Issue 9 (2nd June 2020) - Jehangir, Asad; Tanner, Samuel; Malik, Zubair; Parkman, Henry P.
Abstract: Background: Proximal esophageal striated muscle contractility may be abnormal in patients with esophageal symptoms, but is not assessed in the Chicago Classification (CC) v3.0. We aimed to (a) determine the prevalence of abnormal proximal esophageal contractility in patients with esophageal symptoms; (b) compare proximal esophageal contractility in patients with different esophageal motility disorders; (c) assess the association of abnormal proximal esophageal contractility with esophageal symptoms. Methods: Patients undergoing high‐resolution esophageal manometry (HREM) from 7/2019 to 11/2019 and healthy volunteers (HVs) were studied. Measurements of the proximal esophageal segment included the vigor of contractility of the proximal esophagus (proximal contractile integral/PCI). Patients rated gastrointestinal symptoms' severity. Key Results: HREM was performed on 221 patients (63.8% females, mean age 57.1 ± 1.1 years) and 19 HVs. Mean PCI in HVs was 299.5 ± 30.6 (95% CI 32.3‐566.7 mm Hg . s . cm). Of all patients, 61 (27.6%) had abnormal PCI. HVs and patients with different esophageal motility disorders had significantly different PCI ( P < .01). Type 1 achalasia patients had weaker PCI than patients with absent contractility ( P = .02). Patients with abnormal PCI had more severe dysphagia ( P = .02), nausea ( P = .03), vomiting ( P = .03), and lower bolus clearance ( P < .01) than patients with normal PCI. Conclusions and Inferences: Abnormal PCI was found in a fourth of patients with esophageal symptoms. PCI may be useful to distinguish some esophageal motility disorders. Patients with abnormal PCI had a higher severity of some upper gastrointestinal symptoms than patients with normal PCI. Assessing the proximal esophageal segment on HREM may be useful in characterizing patients with esophageal symptoms. Abstract : Assessing the proximal esophageal segment on HREM may be useful in characterizing patients with esophageal symptoms. Abnormal PCI was found in a fourth of patients with esophageal symptoms. PCI may be useful to distinguish some esophageal motility disorders. Patients with abnormal PCI had a higher severity of some upper gastrointestinal symptoms than patients with normal PCI.